Perioperative outcomes comparing laparoscopic with open repeat liver resection for post-hepatectomy recurrent liver cancer: A systematic review and meta-analysis. (July 2020) - Liang, Yuelong; Lin, Chengping; Zhang, Bin; Cao, Jiasheng; Chen, Mingyu; Shen, Jiliang; Feng, Xu; Xiao, Guangyuan; Pan, Long; Chen, Ke; Maher, Hendi; Cai, Xiujun
Abstract: Background: Repeat laparoscopic hepatectomy (LRH) offers an option for recurrent tumors in liver remnants following an initial liver resection of recurrent hepatocellular carcinoma (HCC), colorectal liver metastasis (CRLM) and cholangiocellular carcinoma (CCC), showing advantages in some outcomes. The objective of the study was to evaluate the feasibility, safety, and potential benefits of LRH in comparison with repeat open hepatectomy (ORH) for recurrent liver cancer. Methods: A systematic review was performed in compliance with the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) and AMSTAR (Assessing the methodological quality of systematic reviews) guidelines. We performed a systematic search of PubMed, Embase, Cochrane Library, and Web of Science to identify studies that compared LRH with ORH from inception to September 30, 2019. Outcomes of interest included operation time, intraoperative estimated blood loss, length of hospital stay, complication rate, transfusion and R0 resection rate. The protocol was registered with the PROSPERO register of systematic reviews. Results: 10 retrospective observational studies were suitable for this analysis, involving 767 patients with 334 undergoing LRH (43.5%) and 433 undergoing ORH (56.5%). Compared with ORH, LRH had less intraoperative blood loss (SMD = −1.03; 95% CI: 1.48 -0.59, P < 0.001), less overall postoperative complications (OR = 0.40; 95% CI: 0.16–0.99, P = 0.048), less major complications (OR = 0.31, 95% CI: 0.15–0.62, P = 0.001), shorter hospital stay (SMD = −0.98; 95% CI: 1.41 -0.54, P < 0.001) and higher R0 resection rate (OR = 2.30, 95% CI: 1.39–3.81, P = 0.001). It was comparable in operation time (WMD = −7.66; 95% CI: 52.50–37.19, P = 0.738), transfusion rate (OR = 0.33; 95% CI:0.11–1.05, P = 0.060), and mortality (OR = 0.76; 95% CI: 0.27–2.18, P = 0.615) between LRH and ORH. Conclusion: Our results indicate that LRH is a safe and effective technique. Benefits, especially less intra-operative blood loss, less complications rate, shorter hospital stay and higher R0 resection, might be offered in the laparoscopic approach. Highlights: LRH is a safe and effective technique in clinical practice. LRH is associated with lower intra-operative blood loss, less complications rate, shorter hospital stays, as well as higher R0 resection. LRH is an appropriate invasive procedure for repeat hepatectomy, providing the satisfactory advantages of minimally invasive surgery.